Yellowstone Lake Nanoarchaeota - Clingenpeel, Scott; Kan, Jinjun; Macur, Rich; Woyke, Tanja; Lovalvo, Dave; Varley, John; Inskeep, William P.; Nealson, Kenneth; McDermott, Tim (Frontiers in Microbiology, 2013)
Considerable Nanoarchaeota novelty and diversity were encountered in Yellowstone Lake, Yellowstone National Park, where sampling targeted lake floor hydrothermal vent fluids, streamers and sediments associated with these vents, and in planktonic photic zones in three different regions of the lake. Significant homonucleotide repeats (HR) were observed in pyrosequence reads and in near full-length Sanger sequences, averaging 112 HR per 1,349 bp clone and could confound diversity estimates derived from pyrosequencing, resulting in false nucleotide insertions or deletions (indels). However, Sanger sequencing of two different sets of PCR clones (110 bp, 1349 bp) demonstrated that at least some of these indels are real. The majority of the Nanoarchaeota PCR amplicons were vent associated; however, curiously, one relatively small Nanoarchaeota OTU (70 pyrosequencing reads) was only found in photic zone water samples obtained from a region of the lake furthest removed from the hydrothermal regions of the lake. Extensive pyrosequencing failed to demonstrate the presence of an Ignicoccus lineage in this lake, suggesting the Nanoarchaeota in this environment are associated with novel Archaea hosts. Defined phylogroups based on near full-length PCR clones document the significant Nanoarchaeota 16S rRNA gene diversity in this lake and firmly establish a terrestrial clade distinct from the marine Nanoarcheota as well as from other geographical locations.